Teaching Narrative Text by Using Preview, Question, Read, State, and Test (PQRST) Technique - Nurul Latifa (English Education Journal, 2018)
This study was aimed to investigate the effects of Preview, Question, Read, State, and Test (PQRST) technique in teaching reading at the first grade students of  MAS Insan Qur’ani Aneuk Batee, Aceh Besar. A quasi experimental research was used and the data were collected through tests and questionnaire. The sample of the research was two classes; religious class as the control class and the science class as the experimental class. The sampling technique used was random sampling.  The data were analyzed by utilizing Mann-whitney test and Levene test for t-test while percentage calculation for questionnaire. Based on the mean score, the experimental groups students had higher reading scores (79) than those of control group (55.5). The students’ reading achievement in both groups was different as indicated by t-score. The result of t-score between two groups is 4.425 with the significant difference score is 0.000 which is lower than α = 0.05. Therefore, it could be concluded that the PQRST technique effectively improved the students’ achievement in reading skill such as main idea, inference, reference, vocabulary and stated detail as well as gave many advantages to the students.